Dental palaeopathology seen through historical, archaeological and biological sources in ancient Herculaneum (79 AD, Italy) - Tanga, Carmen; Viciano, Joan; Monza, Francesca; D'Anastasio, Ruggero; Capasso, Luigi (Medicina Historica, 2020)
In the mid-eighteenth century, King Charles III of Spain started to explore the ruins of the ancient city of Herculaneum. Since then, several medical and surgical instruments made of bronze and iron have been found. The archaeological digs carried out in 1982 in the area corresponding to the ancient shoreline of Herculaneum brought to light not only human remains of about 250 victims killed during the eruption of Vesuvius in the year 79 AD, but also remains of carbonised food and other organic-based materials. Collaboration between different disciplines, including Archaeology, Physical Anthropology, History of Medicine, History of Odontostomatology and Palaeopathology, can provide us with more comprehensive pictures of diseases of the past, not only based on historical, literary and archaeological sources, but also directly on human remains. Through such an interdisciplinary approach, valuable information can be obtained on pathologies of the oral cavity and their distributions, on medical therapies and treatments, and on accessibility to healthcare, including odontostomatological care. An integrated study has allowed us to obtain useful data to reconstruct the habits and lifestyles of the ancient people of Herculaneum. In this report, three cases are presented to illustrate the importance of integration of data inferable from such different sources.